Factors Related to the Level of Depression and Suicidal Behavior Among Men With Diagnosed Depression, Physically Ill Men, and Healthy Men - Kielan, Aleksandra; Jaworski, Mariusz; Mosiołek, Anna; Chodkiewicz, Jan; Święcicki, Łukasz; Walewska-Zielecka, Bożena (Frontiers in Psychiatry, 2021)
Depression is the most common psychiatric disorder in people who die by suicide. Awareness of risk factors for suicide in depression is important for clinicians. The study was aimed at establishing models of depression and suicidal behavior risks among men from three different groups – in men with depressive disorder, in comparison to men with physical disorder and healthy men. A total of 598 men were included into the study. Questionnaires used in research model: test with sociodemographic variables, AUDIT Test, Fagerström Test, Generalized Self-Efficacy Scale (GSES), Inventory for Measuring Coping with Stress (Mini-COPE), Resilience Evaluation Questionnaire (KOP-26), Suicide Behaviors Questionnaire - Revised (SBQ-R) by Osman and Gotland Male Depression Scale. In men with depression, the strong protective factors against depression and suicidal behavior were as follows: vocational education, active coping, turning towards religion, social competence for resilience and bachelor status. The risk factors in this group were as follows: unemployed status, student status, low satisfaction with financial situation, having children, history of mental disorders in family, alcohol addiction and seeking instrumental support. In the group of men with physical disorders, the following protection factors were identified: medium or small city as a place of living, active coping, venting and personal competence. The following risk factors were identified in this group: psychiatric treatment in the past. In the group of healthy men, the following protective factors were identified: medium city as a place of living, positive reappraisal, planning abilities , personal and social competence for resilience. In this group the following risk factors were identified: vocational and higher education, student status, satisfaction with financial situation, having more than 1 children, occurrence of mental disorders in family, occurrence of alcohol abuse in family and use of psychoactive substances as a strategy of dealing with stress. The risk factors identified in this study should be included in clinical assessment of depression and suicidal behavior risk in male patients. There are some protective factors identified, including: productive coping, personal and social competences, which can be developed and should be especially considered and strengthened in mental health promotion programmes aimed at men.